Doppler broadening of neutron elastic scattering cross section using SCLM(α,β) thermal scattering laws - Bengoechea Fernández Aitor; Noguere Gilles; Bernard David (EPJ Nuclear Sciences & Technologies)
In nuclear data processing codes, Free Gas and Crystal Lattice Models are used to account for temperature effects in neutron elastic scattering cross sections. A somewhat arbitrary thermal cutoff energy is introduced to define the energy ranges of application of the two models, given that the Crystal Lattice Model in processing codes can only be applied to constant cross sections. Despite works performed on 238U, no algorithm reported in the literature provides a unified Crystal Lattice Model valid below and above the thermal cutoff energy. This paper presents two new Doppler models, namely α0 and α′ models. The α0 model is able to account for the Doppler broadening effects in the resonance range of the neutron cross sections, while the α′ model provides a unified description of the Doppler effect over the entire energy range of interest for nuclear reactor applications. The performances of the models are illustrated with 238U, 240Pu and 237Np.